Multi-regional multi-objective optimization of an algal biofuel polygeneration supply chain with fuzzy mathematical programming - Ubando, Aristotle T. (Animo Repository, 2014)
A polygeneration approach is proposed to improve the economic viability of algal biofuel production through simultaneous production of co-products (i.e. electricity, heat, and other biochemicals). A multi-regional polygeneration supply chain consists of various array of processing plants in producing multiple bioenergy products given spatial constraints of each plant found in different regions. The inherent complexity of the polygeneration compounds the difficulty of designing the composite network of processing plants in multi-regions. Optimizing the design flow of the polygeneration supply chain considers multiple objectives, such as satisfying product demand, maximizing economic performance, and minimizing environmental footprint. In addition, the optimal strategic capacity design of the supply and distribution of biodiesel across multi-regions are considered. This study uses a fuzzy mathematical programming model to generate an optimized design of the polygeneration supply chain while satisfying all objectives. The developed model is demonstrated using a modified industrial case study comparing two cultivation alternatives. Results showed that all fuzzy multi-objective goals are satisfied and the flat-plate photobioreactor is the preferred cultivation system in terms of environmental footprints and economic performance. Copyright © 2014 by ASME.